2010
DOI: 10.1111/j.1472-4642.2009.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

The worldwide expansion of the Argentine ant

Abstract: Aim  The aim of this study was to determine the number of successful establishments of the invasive Argentine ant outside native range and to see whether introduced supercolonies have resulted from single or multiple introductions. We also compared the genetic diversity of native versus introduced supercolonies to assess the size of the propagules (i.e. the number of founding individuals) at the origin of the introduced supercolonies.Location  Global.Methods  We used mitochondrial DNA (mtDNA) markers and micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
135
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(146 citation statements)
references
References 102 publications
11
135
0
Order By: Relevance
“…Jump dispersal from the native range (i.e., the primary source) played a major role at the initial stage of the expansion of the Argentine ant (16), but now the dispersion of propagules from secondary sources (i.e., established populations in the introduced range) accounts for much of the spread of the species worldwide (15,16). Further information on dispersal pathways (sensu ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jump dispersal from the native range (i.e., the primary source) played a major role at the initial stage of the expansion of the Argentine ant (16), but now the dispersion of propagules from secondary sources (i.e., established populations in the introduced range) accounts for much of the spread of the species worldwide (15,16). Further information on dispersal pathways (sensu ref.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have examined the distribution and dispersal pathways of this invasive ant (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) and described the range limits at regional and global scales (20,(23)(24)(25)(26)(27)(28). However, most of these studies relied on simple environmental niche models or described the current distribution of the species using only partial records.…”
mentioning
confidence: 99%
“…However, population genetics predicts that invasive species might collapse owing to inbreeding depression or an inability to adapt to their new environment [12]. Previous genetic studies have revealed that the New Zealand population of Argentine ants has among the lowest recorded genetic diversity of any introduced Argentine ant population worldwide, indicative of the entire supercolony having arisen from an incursion of just one nest [7,12]. Low genetic diversity, perhaps in combination with pathogens [13] or a depletion of local resources [10], is a candidate mechanism for these collapses.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, introduction into new habitats may yield consequences similar to those of conventional inbreeding in terms of increasing the frequency of detrimental phenotypes owing to recessive deleterious mutations. For example, all introduced populations of invasive ants studied so far possess fewer alleles than native populations [11,[15][16][17][18][19], and introduced populations of the fire ant Solenopsis invicta [8,15] produce high proportions of diploid males.…”
Section: Introductionmentioning
confidence: 99%